A sound engineer's guide to audio test and measurement - Ballou, Glen (Amsterdam : Elsevier Science, 2009)
This book offers a quick guide and complete reference to the fundamentals of test and measurement for all aspects of sound engineering. Including electrical and acoustic testing, measurement systems, levels, methods, protecting the ear, units of measurement and standards, this guide comes with and multiple tables to ensure quick easy access to information and illustrate points this is a must have reference for all audio engineers.
Section 1. Test and Measurement, Pat Brown -- Section 2. What's the Ear For? How to Protect It, Les Blomberg, Noland Lewis -- Section 3. Fundamentals and Units of Measurement, Glen Ballou.
Includes bibliographical references and index.
Keywords: ACOUSTICAL ENGINEERING